2017
DOI: 10.3389/fpsyg.2017.01542
|View full text |Cite
|
Sign up to set email alerts
|

Subliminally and Supraliminally Acquired Long-Term Memories Jointly Bias Delayed Decisions

Abstract: Common wisdom and scientific evidence suggest that good decisions require conscious deliberation. But growing evidence demonstrates that not only conscious but also unconscious thoughts influence decision-making. Here, we hypothesize that both consciously and unconsciously acquired memories guide decisions. Our experiment measured the influence of subliminally and supraliminally presented information on delayed (30–40 min) decision-making. Participants were presented with subliminal pairs of faces and written … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 102 publications
0
5
0
Order By: Relevance
“…[23][24][25][26][27][28] These findings confirm newer theoretical claims 3,4,8 that the sole premise for episodic encoding through hippocampus is not consciousness but a task that calls upon the core computational competence of the hippocampus, namely, the rapid formation of new and flexible associations. When applying such tasks, unconscious episodic encoding and retrieval was revealed using subliminal word pairs, 23,29,30 subliminal face-word pairs, 24,[31][32][33] and subliminal objects in space. 26 Moreover, participants inferred unconsciously that two ordinarily unrelated words A-C are semantically related based on the preceding subliminal encoding of discontinuously flashed subliminal word pairs A-B and B-C. 34,35 Furthermore, subliminal associative encoding encompassed the encoding of complex visuospatial second-order sequences, 36 the understanding of causal events, 37 and narratives from spatial-temporal movement patterns.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[23][24][25][26][27][28] These findings confirm newer theoretical claims 3,4,8 that the sole premise for episodic encoding through hippocampus is not consciousness but a task that calls upon the core computational competence of the hippocampus, namely, the rapid formation of new and flexible associations. When applying such tasks, unconscious episodic encoding and retrieval was revealed using subliminal word pairs, 23,29,30 subliminal face-word pairs, 24,[31][32][33] and subliminal objects in space. 26 Moreover, participants inferred unconsciously that two ordinarily unrelated words A-C are semantically related based on the preceding subliminal encoding of discontinuously flashed subliminal word pairs A-B and B-C. 34,35 Furthermore, subliminal associative encoding encompassed the encoding of complex visuospatial second-order sequences, 36 the understanding of causal events, 37 and narratives from spatial-temporal movement patterns.…”
Section: Introductionmentioning
confidence: 99%
“…[42][43][44][45] Because visual input is stronger during supraliminal versus subliminal encoding, we expected steeper local maxima in brain activation and broader activation clusters during conscious versus unconscious processing. 23,35,[46][47][48][49][50] We also hypothesized that unconscious retrieval performance would remain stable with increasing information load, 23,24,26,[29][30][31][32][33][34][35] while conscious retrieval performance would drop. Finally, we measured the participants' habitual decision style-intuitive versus deliberative-to account for the possibility that habitually intuitive decision makers would outperform deliberative decision makers in the unconscious condition that required intuitive decisions at test.…”
Section: Introductionmentioning
confidence: 99%
“…In our opinion, the sensitivity of the P1 amplitude stems from unconscious attentional capture of reward‐related stimuli during the option assessment stage, which is supported by previous findings that attention, but not awareness, is essential to control motivated behavior (Mastropasqua & Turatto, ). Additionally, previous studies have revealed that subconscious contextual reward cues produce biases in decision making (Pessiglione et al, ; Ruch, Herbert, & Henke, ). Furthermore, this finding implies that value‐based decision preference might have been developed before human species consciously attended to the options.…”
Section: Discussionmentioning
confidence: 97%
“…For example, after subliminal exposure to ‘winter‐red’ and ‘red‐computer’ pairs, response to the target ‘winter‐computer’ was facilitated. Meanwhile, subliminal pairings of a face with an occupation label, also influenced occupation‐related judgement towards the face when it was later presented as a visible target (Degonda et al, 2005; Duss et al, 2011; Henke, Mondadori, et al, 2003; Henke, Treyer, et al, 2003; Ruch et al, 2016, 2017; Züst et al, 2015). Furthermore, the authors also remarkably proposed the integration of complex relational/visuospatial information between various subliminal visual scenes/items (Nickel et al, 2015; Schneider et al, 2021; Wuethrich et al, 2018).…”
Section: Current Reports Of Subliminal Integrationmentioning
confidence: 99%